2020
DOI: 10.3390/photonics7030053
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplasmonics in High Pressure Environment

Abstract: An explosion in the interest for nanoplasmonics has occurred in order to realize optical devices, biosensors, and photovoltaic devices. The plasmonic nanostructures are used for enhancing and confining the electric field. In the specific case of biosensing, this electric field confinement can induce the enhancement of the Raman signal of different molecules, or the localized surface plasmon resonance shift after the detection of analytes on plasmonic nanostructures. A major part of studies concerning to plasmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 100 publications
(124 reference statements)
0
5
0
Order By: Relevance
“…Pressure is an important variable to consider in the study of the fundamental properties of nanoparticles and the role of size and increased surface area in determining the said properties. Size dependence in high-pressure phase diagrams has been observed in metallic and semiconductor nanocrystals, and similar studies have reported intriguing pressure-dependent optical and mechanical properties of nanocrystals and their assemblies.…”
Section: Introductionmentioning
confidence: 78%
“…Pressure is an important variable to consider in the study of the fundamental properties of nanoparticles and the role of size and increased surface area in determining the said properties. Size dependence in high-pressure phase diagrams has been observed in metallic and semiconductor nanocrystals, and similar studies have reported intriguing pressure-dependent optical and mechanical properties of nanocrystals and their assemblies.…”
Section: Introductionmentioning
confidence: 78%
“…Since their emergence, plasmonic nanomaterials have been among the fastest-growing subfields of optical materials. Resonant optical absorption and support of highly localized strong electromagnetic fields have yielded many applications for these materials, such as active and passive optical elements, sensors, or energy conversion to mention but a few examples. , One direction owing to the opportunity of tailoring the optical absorption is the development of various types of optical filters. , For instance, customizing structural properties of plasmonic nanomaterials to design their spectral response has enabled high-quality color filters . However, in many cases, this has come with the cost of necessary top-down nanopatterning.…”
Section: Introductionmentioning
confidence: 99%
“…The plasmon resonance of gold nanoparticles has been previously monitored by optical absorbance spectroscopy during compression in a diamond anvil cell. , The effects observed in plasmonic nanoparticles under compression are attributed to a combination of changes in the dielectric function of the metal, ,,, changes in the refractive index of the pressure medium, ,,, changes in the crystallinity of the metal, ,, and changes in the shape of the particles themselves. ,,, The relative contribution of each of these effects depends on the type of compression applied and the particles under investigation. For hydrostatic compression of particles, shape change and plastic deformation are negligible, so the plasmon response is dominated by changes in the dielectric function of the metal and changes in the refractive index of the surroundings .…”
Section: Introductionmentioning
confidence: 99%